PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL WADAH LIPATAN DAUN UNTUK MENINGKATKAN KETERAMPILAN SISWA KULINER FASE E SMK NEGERI 3 KEDIRI - Della Riswanda; Luthfiyah Nurlaela; Febriani Lukitasari; Hanif Naufal Ahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determinate: 1) the feasibility of the material and media video tutorial leaf folding container; 2) the effectiveness of video tutorial learning media in improving students skills. This study uses the 4D Thiagarajan model which is carried out up to the third stage. The research stages include the following stages: define, design, develop. Assesment of the suitability of learning materials and media using a scale likert 1-4. The object of the research is a leaf folding video tutorial learning media. The research subject are students of SMK Negeri 3 Kediri culinary expertise program phase E. Data analysis of the effectiveness of the learning media using N-Gain. The results of this study indicate that: 1) validation by material experts obtained an average score of 88% with criteria of “Very Appropiate”; 2) validation results by media experts obtained an average score of 87% with criteria of “Very Appropiate”; 3) the results of the assessment of the effectiveness of learning media in improving students skills showed an increase as evidenced by the results pre-test of 65,44 and post test 79,94%. Analysis using N-Gain the result was 0,30 with a “Medium” criterion. Thus, the develop leaf folding video tutorial learning media is highly suitable for implementation inthe learning process and quite effective in improving student skills.